Management by Walking Around as an Approach to Improving Organizational Excellence in Media Institutions - Durrah, Omar; Eltigani, Mohammed Osman; Gharib, Moaz; Hannawi, Souzan (Journal of Economic, Administrative and Legal Sciences, 2020)
The current study investigates the extent of the contribution of five facets of management by walking around (MBWA) — discovering facts, communication, motivation, creativity, and feedback — to improving organizational excellence in media institutions in the Sultanate of Oman. Especially as these institutions suffer from a lack of communication and interaction between their management and their employees. The descriptive analytical approach was used in this study. Using a simple random sampling technique, data were collected using a questionnaire from 260 respondents working as administrative staff in three media institutions: The Directorate General of Media, the Omani News Office in Dhofar Governorate, and the General Authority for Radio and Television. To test the study hypotheses, the data were analyzed using Structural Equation Modeling (SEM) by AMOS software. The results revealed that, of the five facets investigated, three dimensions of MBWA (namely discovering facts, communication, and feedback) have a positive and significant impact on organizational excellence, while motivation and creativity do not appear to affect organizational excellence. This study, therefore recommends working to create a supportive environment for applying MBWA in media institutions and educating managers in these media institutions on the importance of MBWA through workshops, training courses, and conferences to reach excellence in these institutions.
Keywords: management by roaming; Management by Walking Around; Organizational Excellence; Media Institutions; Sultanate of Oman